Fish consumption patterns and hair mercury levels in children and their mothers in 17 EU countries - Castaño, Argelia; Cutanda, Francisco; Esteban, Marta; Pärt, Peter; Navarro, Carmen; Gómez, Silvia; Rosado, Montserrat; López, Ana; López, Estrella; Exley, Karen; Schindler, Birgit K; Govarts, Eva; et al. (Environmental research, 2015)
The toxicity of methylmercury (MeHg) in humans is well established and the main source of exposure is via the consumption of large marine fish and mammals. Of particular concern are the potential neurodevelopmental effects of early life exposure to low-levels of MeHg. Therefore, it is important that pregnant women, children and women of childbearing age are, as far as possible, protected from MeHg exposure. Within the European project DEMOCOPHES, we have analyzed mercury (Hg) in hair in 1799 mother-child pairs from 17 European countries using a strictly harmonized protocol for mercury analysis. Parallel, harmonized questionnaires on dietary habits provided information on consumption patterns of fish and marine products. After hierarchical cluster analysis of consumption habits of the mother-child pairs, the DEMOCOPHES cohort can be classified into two branches of approximately similar size: one with high fish consumption (H) and another with low consumption (L). All countries have representatives in both branches, but Belgium, Denmark, Spain, Portugal and Sweden have twice as many or more mother-child pairs in H than in L. For Switzerland, Czech Republic, Hungary, Poland, Romania, Slovenia and Slovakia the situation is the opposite, with more representatives in L than H. There is a strong correlation (r=0.72) in hair mercury concentration between the mother and child in the same family, which indicates that they have a similar exposure situation. The clustering of mother-child pairs on basis of their fish consumption revealed some interesting patterns. One is that for the same sea fish consumption, other food items of marine origin, like seafood products or shellfish, contribute significantly to the mercury levels in hair. We conclude that additional studies are needed to assess and quantify exposure to mercury from seafood products, in particular. The cluster analysis also showed that 95% of mothers who consume once per week fish only, and no other marine products, have mercury levels 0.55 μg/g. Thus, the 95th percentile of the distribution in this group is only around half the US-EPA recommended threshold of 1 μg/g mercury in hair. Consumption of freshwater fish played a minor role in contributing to mercury exposure in the studied cohort. The DEMOCOPHES data shows that there are significant differences in MeHg exposure across the EU and that exposure is highly correlated with consumption of fish and marine products. Fish and marine products are key components of a healthy human diet and are important both traditionally and culturally in many parts of Europe. Therefore, the communication of the potential risks of mercury exposure needs to be carefully balanced to take into account traditional and cultural values as well as the potential health benefits from fish consumption. European harmonized human biomonitoring programs provide an additional dimension to national HMB programs and can assist national authorities to tailor mitigation and adaptation strategies (dietary advice, risk communication, etc.) to their country's specific requirements.
Keywords: dospělí; Hair; průzkumy a dotazníky; Europe; Female; Sea fish; Feasibility Studies; Seafood; dítě; chemické látky znečišťující vodu; Urban Population; Food Preferences; methylortuťné sloučeniny; vlasy, chlupy; Adult; potrava z moře (živočišná); ženské pohlaví; monitorování životního prostředí; Food Contamination; Surveys and Questionnaires; Water Pollutants, Chemical; Mercury in hair; lidé; Evropa; Pilot Projects; Shellfish; pilotní projekty; Human Biomonitoring; kontaminace potravin; Data Interpretation, Statistical; matky; studie proveditelnosti; venkovské obyvatelstvo; interpretace statistických dat; Mothers; Methylmercury Compounds; městské obyvatelstvo; Environmental Monitoring; lidé středního věku; Child; Middle Aged; Rural Population; preference v jídle; Seafood products; Humans